Pengambilan Keputusan Manajemen: Tinjauan Self-Esteem Dan Eskalasi Komitmen - Freitas, Jorge Ribeiro; Utami, Intiyas (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2018)
The research carried out in East Timor aims at 1) To determine decision making on the limitations of working capital, human resources, technology, and product marketing, with a review of self-esteem and commitment escalation, and 2) To determine management decisions on similar imported products from outside with a review of self-esteem and escalation of commitment. This type of research is qualitative in 5 (five) informants using a case study approach. The results showed that despite having capital constraints but for furniture industry owners having high self-esteem, they would continue the furniture industry, one of which was to sell personal assets to increase capital. The owner of the furniture industry still produces highly competitive furniture products, because the workforce has the skills to use the production equipment owned to produce furniture according to consumer demand. Furthermore, marketing furniture products made in production, verbal promotion between owners and customers to fellow customers with information about product prices. Self-esteem and escalation of commitments occur when the industry experiences difficulties in the capital. The results of this study indicate that furniture industry owners have high self-esteem that can produce furniture that has high quality, different from products imported from other countries, according to consumer demand. Self-esteem is an important resource to encourage industrial owners to increase their commitment to maintain highly competitive product quality.Â